Pengaruh Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan - Pramitha, Ayu; Rafika Sari; Kgs. M. Nurkholis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to analyze the partial and simultaneous influence of the accounting information system and internal control on the quality of PT's financial reports. PP London Sumatra Indonesia Tbk. SEI Lakitan POM Branch. This research uses quantitative analysis techniques and the data sources used are primary data and secondary data. The analytical method used is multiple regression analysis, t-test, f test and coefficient of determination (R^2). The results of testing the accounting information system variable can be seen from a significance level that is smaller than 0.05 and the t_count value is greater than t_table, namely 4.851. Apart from that, the results of testing the internal control variables can be seen from a significance level that is smaller than 0.05 and the calculated t_value is greater than t_table or 6.465. Thus, it can be concluded that partially the accounting information system variables and internal control variables have a significant positive effect on the quality of PT's financial reports. PP London Sumatra Indonesia Tbk. SEI Lakitan POM Branch. Simultaneous testing shows that the f_count value is greater than f_table or 23.371. Thus, it can be concluded that simultaneously (together) the variables of the accounting information system and internal control have a significant positive effect on the quality of financial reports at PT. PP London Sumatra Indonesia Tbk. SEI Lakitan POM Branch.